Atrial Septal Defect (Secundum): A Case Report of a Family (Cardiovascular Journal, 2011)
Atrial Septal Defect (ASD) Secundum type was detected in a female patient Miss S.A at 20 years of age. She was operated from Birla Heart Research Center, Kolkata India in 1995.She got married after two years. Her son Master Z.S was also diagnosed as ASD secundum and was operated from Narayana Hrudayalaya Institute of Cardiac Science, Bangalore, India in the year 2005 when he was 8 years old. Her daughter was born in the same year and was diagnosed as a case of large ASD secundum (almost common atrium). This girl is now waiting for device closure from Combined Military Hospital (CMH) Dhaka, but her weight is still low for such procedure. This family is a rare family where mother and both children have ASD secundum and possibility of genetic inheritance was strongly suspected which lead to the writing of this report. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8173 Cardiovasc. j. 2009; 1(2) : 226-228